Dynamic Response Of Guyed Crane Girder Structure Induced By Moving Loads - Yazid, Edwar; Parman, Setyamartana; Fuad, Khairul (2009)
Dynamic response of crane girder supported by pairs of forestays induced by moving loads is studied in this paper. Each forestay is modeled as an equivalent spring with added mass while girder structure is modeled using the finite element method. Direct integration method (Newmark-B) is employed in calculating its dynamic response. Parametric study such as the speed, mass of the moving load, forestays position, viscous damping as well as velocity histories of the moving load that affect vibration of the structure are investigated. The results obtained are then compared with the results of a commercial finite element package ANSYS and good agreement is found.